EFFECTIVENESS OF PEER-BASED HEALTH EDUCATION WITH AUDIO-VISUAL MEDIA IN ENHANCING EMERGENCY TRIAGE COMPETENCE - Ria Anggraini; Intan Munawaroh; Manggar Purwacaraka; Berlian Yuli Saputri (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Emergency conditions necessitate prompt and appropriate management to mitigate the risks of disability and mortality. A fundamental component of emergency care is triage, which serves to prioritise patient treatment based on the severity of their condition and guide the necessary clinical interventions. This study aimed to assess the effectiveness of peer-led health education supported by audio-visual media in improving students' comprehension of emergency triage procedures.Methods: A quasi-experimental study with a non-equivalent control group pretest-posttest design was implemented. The research population comprised second-semester nursing students from STIKES Hutama Abdi Husada Tulungagung. A purposive sampling method was used to select 41 participants. The educational intervention was delivered through peer-led sessions and supplemented with audio-visual media. Data were gathered using a validated structured questionnaire and analysed employing the Wilcoxon signed-rank test and the Mann-Whitney U test.Results: Analysis using the Wilcoxon signed-rank test yielded a statistically significant result (p = 0.000) in both intervention groups, demonstrating that the health education provided had a meaningful impact on students' understanding of emergency triage. Furthermore, the Mann-Whitney U test indicated a mean rank of 35.43 for participants in the peer education group and 47.57 for those in the audio-visual group, with a significance level of p = 0.019. Conclusion: The findings confirm that both peer-led and audio-visual-based health education methods are effective in increasing nursing students' knowledge of emergency triage. Nevertheless, the audio-visual approach demonstrated superior outcomes and is, therefore, recommended as the preferred strategy for enhancing triage competency in educational settings.